Delimitation of the inclusive competency profile necessary in initial training in elementary education grades - Garcia-Vallès, Xenia (Innovaciones Educativas, 2020)
One of the factors that influence the development of inclusive processes in schools is the initial teacher training in the field of inclusive education. The university, as a training center, has chosen to combine the two existing models: a more transversal model of training on inclusive education and a more specific one. The choice of training models is related to the conception of inclusive education. However, it would be relevant to identify what are the necessary competencies so that future teachers can implement inclusive processes in schools. In this sense, the article aims to identify the key skills in inclusive education (CEI competences for inclusive education – acronym in Spanish) for initial training (FI – acronym in Spanish) in elementary education grades. Through the Delphi method, in which experts and professionals from the field of inclusive education have participated, the results are committed to university training in the Elementary Education Degree, where transversal competences related to teamwork, communication, energization of supports, collaboration, leadership, conflict resolution and a critical and positive attitude that allows inclusive educational processes to be achieved